Eligibility to Use the Fund's Facilities for Concessional Financing, 2020. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2020)
This paper concludes that the existing framework remains broadly appropriate, but proposes methodological refinements to improve the assessment of market access, clarifies how serious short-term vulnerabilities are assessed, and proposes a modest extension of the transition period before graduation decisions become effective.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet